2007
DOI: 10.1175/2007jhm791.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study to Investigate the Relationship between Moisture Convergence Patterns and Orography in Central Mexico*

Abstract: This study examines small-scale orographic effects on atmospheric moisture convergence at the ridgevalley scale in the Grande de Santiago River basin in central Mexico during a major monsoon storm on 13-14 August 1999. The simulation was performed using a coupled land-cloud resolving model on three nested grids (at 12-, 3-, and 1-km resolutions). The specific objective is to investigate the physical mechanisms that explain the regional space-time organization of orographic precipitation and cloudiness identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 74 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…6c (on the mountain peak) is where the small-scale precipitation is observed. Previous studies also showed a strong relationship between surface MFC and the precipitation (Becker et al 2011;Bhushan and Barros 2007;Holman and Vavrus 2012). This convergence can have multiple reasons, such as moisture transport from the moist air impinging on the mountain and local evaporation over the mountain peak where precipitation is observed.…”
Section: Discussion Of Idealized Setup Resultsmentioning
confidence: 83%
“…6c (on the mountain peak) is where the small-scale precipitation is observed. Previous studies also showed a strong relationship between surface MFC and the precipitation (Becker et al 2011;Bhushan and Barros 2007;Holman and Vavrus 2012). This convergence can have multiple reasons, such as moisture transport from the moist air impinging on the mountain and local evaporation over the mountain peak where precipitation is observed.…”
Section: Discussion Of Idealized Setup Resultsmentioning
confidence: 83%
“… Frame and Markowski [2006] found that the cold pool of a squall line system passing over a relatively low mountain range can undergo this effect, producing a leeward side regeneration of the squall line at the location of the hydraulic jump (Figure 11). Studying conditions in the Sierra Madre in Mexico, Bhushan and Barros [2007] showed how a hydraulic jump associated with synoptic‐scale flow over a region of larger mountains can produce a line of moisture convergence and trigger convection in a valley.…”
Section: Basic Mechanisms By Which Hills and Mountains Affect Precipimentioning
confidence: 99%
“…The geometry and orientation of topographic features dynamically modulates synoptic scale systems by a broad variety of physical mechanisms, including orographic uplift, blocking, differential heating, moisture convergence, convective triggering, and gravity waves (see, e.g., Barros and Lettenmaier [], Roe [], Smith [], and Houze [], for review). Stationary orographic forcing has been shown to dominate the hydroclimatology over massive mountainous regions at climate scales and can give rise to some of the most extreme rainfall intensities and gradients at weather time scales [e.g., Barros and Lettenmaier , ; Lang and Barros , ; Barros and Lang , ; Garreaud et al ., ; Barros et al ., , ; Roe , ; Zipser et al ., 2006; Bhushan and Barros , ; Giovannettone and Barros , ; Romatschke and Houze , ; Rasmussen and Houze , ; Houze , ]. The resulting moisture fields are modified by numerous nonlinear interactions giving rise to complex orographic cloud and rainfall spatial patterns with variability over a wide scale spectrum [ Harris et al ., ; Barros et al ., , ; Nykanen , ; Nogueira et al ., ].…”
Section: Introductionmentioning
confidence: 99%